PENDIDIKAN PARTISIPATIF BAGI KELOMPOK WANITA TANI MENGOLAH KOLANG-KALING MENJADI ANEKA MAKANAN BERBASIS KONSEP ZERO WASTE - Desnita; Iryani; Iswendi; Yusmaita, Eka; Nazifah, Naurah (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2023)
Nagari Batu Bulek Tanah Datar district has an extensive sugar palm plantation, which stretches along the slopes of Mount Sago. However, they do not process the potential for an abundant harvest, because the community does not have the knowledge and skills to process fro and fro into various foods. So that abundant natural resources do not bring prosperity to them. Participatory assistance has been carried out to hone the knowledge and skills of the Lotus Farmers Group (KWT) and Cempaka Mekar Nagari Batu Bulek to apply high sugar preservation technology and natural ingredients, based on the zero waste concept. Before receiving assistance, this KWT member was only able to process fruit and fro into compote and ice and fro. After getting assistance, now the KWT members are proficient in making various jams and fro as well as dragon fruit syrup and eco-enzymes from peels and unused fruit scraps.